Hubungan Pengetahuan dan Sikap Karyawan Perkebunan Kelapa Sawit dengan Perilaku Aman - Muhammad Reza Amrullah; Arifin Arifin; Maharso Maharso (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2019)
Abstract: The Relations Of Oil Palm Plantations Employee Knowledge and Attitude With Safety Behaviour. The Efforts to implement safety and health at work, Based on the results of the study showed that the work accident in the plantation related with the form of working operations in the plantations begin from the process of replanting, planting, plant maintenance to the production process. The purpose of the research is to find the relations Of Oil Palm Plantations Employee Knowledge and Attitude With Safety Behaviour in PT. GMK West Plantation Batu Ampar Sub-district Tanah Laut Regency, the benefit of this research is as an information and evaluation material to know the factors influencing employees with the relations of safety behavior.The research method used is an analytical survey with cross sectional approach, the population in this study amounted to 540 people, and the sample is 50 people. Data analysis is using test (Chi-Square).The results of the study showed: (1) good knowledge 90%, (2) good attitude 60%, (3) good behavior 60%, (4) knowledge (p = 0,643), (5) attitude (p = 0,000). There is no relations of knowledge and there is a relations of oil palm plantation employee attitude with safety behavior in PT. GMK West Plantation Batu Ampar Sub-District Tanah Laut Regency.